2023
DOI: 10.1111/jdv.19588
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic criteria explained by LC‐OCT: Negative maple leaf‐like areas

Gerardo Palmisano,
Carmen Orte Cano,
Margot Fontaine
et al.

Abstract: Dear Editor, Basal cell carcinoma (BCC) is the most common malignant tumour and accounts for 75% of all skin cancers. 1 Nowadays, BCC diagnosis mainly relies on dermoscopy. 2 The dermoscopic features of BCC are diverse and depend on tumour's subtype, location, and depth, and on patient's phototype, gender, and age. 3-5 A new dermoscopic criterion for BCC, the 'negative maple-leaf-like areas' (NMLLAs), was recently proposed by Imbernón-Moya et al. 6 NMLLAs are round, nonpigmented bulbous structures with a homog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…From our results, maple-leaf-like areas corresponding to medium-reflective lobules with maple-leaf shapes were appreciable in 12% of cases considering both dermoscopy and LC-OCT, thus showing a high level of concordance ( p < 0.001). Although they were not evaluated in our study, Palmisano et al [ 27 ] revealed a correlation between negative maple-leaf shape areas and deep hypopigmented tumor lobules.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…From our results, maple-leaf-like areas corresponding to medium-reflective lobules with maple-leaf shapes were appreciable in 12% of cases considering both dermoscopy and LC-OCT, thus showing a high level of concordance ( p < 0.001). Although they were not evaluated in our study, Palmisano et al [ 27 ] revealed a correlation between negative maple-leaf shape areas and deep hypopigmented tumor lobules.…”
Section: Discussionmentioning
confidence: 56%
“…Based on previous works [ 27 ] and our experience, we attempted to assess the association between dermoscopy and LC-OCT using ten-point criteria. Overall, we found that most dermoscopic aspects evaluated were also appreciable under LC-OCT, and no statistically significant differences were found between them ( p > 0.005).…”
Section: Discussionmentioning
confidence: 99%